2020
DOI: 10.1016/j.pscychresns.2020.111135
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiological reward system in Prolonged Grief Disorder (PGD): A systematic review

Abstract: Prolonged Grief Disorder (PGD) is a debilitating condition affecting between 7% and 10% of bereaved individuals. Past imaging and psychological studies have proposed links between PGD's characteristic symptoms -in particular, profound yearning -and the neural reward system. We conducted a systematic review to investigate this connection. On December 19, 2019, we searched six bibliographic databases for data on the neurobiology of grief and disordered grief. We excluded studies of the hypothalamic-pituitary-adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 99 publications
2
27
0
2
Order By: Relevance
“…Research over the past quarter century has shown not only that a small but substantial proportion of grief reactions can be severe, disabling, and endure beyond normal expectations, but that they may respond only to specialist treatment. Specifically, studies have documented that certain grief symptoms are distinct from those of bereavement-related depression [6][7][8][9] , have idiosyncratic neurobiological 10 and clinical [11][12][13] correlates, can persist unabated for months or even years 8,14 , prove distressing and dysfunctional [14][15][16] , and may only respond to targeted intervention 17,18 . Thus, there exists a substantial and mounting body of evidence in support of a psychiatric syndrome of maladaptive grief.…”
mentioning
confidence: 99%
“…Research over the past quarter century has shown not only that a small but substantial proportion of grief reactions can be severe, disabling, and endure beyond normal expectations, but that they may respond only to specialist treatment. Specifically, studies have documented that certain grief symptoms are distinct from those of bereavement-related depression [6][7][8][9] , have idiosyncratic neurobiological 10 and clinical [11][12][13] correlates, can persist unabated for months or even years 8,14 , prove distressing and dysfunctional [14][15][16] , and may only respond to targeted intervention 17,18 . Thus, there exists a substantial and mounting body of evidence in support of a psychiatric syndrome of maladaptive grief.…”
mentioning
confidence: 99%
“…The first reason is that PGD has been shown to demonstrate a distinct neural profile when compared to MDD or PTSD [15]. In contrast to conceptualizing PGD as a mood disorder such as MDD or a stress response syndrome such as PTSD, there is emerging evidence to suggest that PGD may be conceptualized as a reward dysfunction disorder, with the deceased person as the rewarding stimulus for whom the bereaved person yearns [16]. PGD, as noted above, is at its core a disorder of attachment and a craving and yearning for the deceased from whom they are separated (resulting in significant separation distress).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Neurobiologically, numerous studies suggest that there are associations between symptoms of PGD and the reward pathway, which is the same pathway primarily responsible for addiction [ 16 ]. The reward pathway refers to a group of interconnected structures in the brain that uses dopamine as a signal to modulate the experience of reward.…”
Section: Introductionmentioning
confidence: 99%
“…Einem Review zufolge [33] Gestützt wird die Annahme, dass ein primär durch negative Emotionen geprägter langanhaltender Zustand nach einem Verlusterlebnis mit einer Belohnungsdysregulation einhergehen kann, allerdings durch ähnliche Befunde bei PGD, der anhaltenden Trauerstörung [41]. So zeigen sich bei PGD in bildgebenden Studien ebenfalls Aktivierungen des Belohnungssystems, der Basalganglien, des orbitofrontalen Kortex und der Amygdala, ähnlich wie bei den Liebeskummerstudien und ähnlich wie in Studien zu Suchterkrankungen.…”
Section: Neurobiologie Des Liebeskummersunclassified